The concept of us and them: communitarianism and the rise of populist politics - Cetin, Ihsan (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This article mainly focuses on the existence and/or construction of “the others” as one of the main pillars of populist politics which have risen in various countries during recent years. Populist rhetoric gains its political power over the social groups or individuals who are identified as “the others” and who differ from the majority by their identities, believes, traditions etc. Populist discourse is also supported by the notion of communitarianism. In this sense, this article basically examines the social dynamics which reinforcing the populist discourse. Some structural factors, such as international migration and increasing global migration, global inequality created by neo-liberal policies and structural adjustment programs, and the changing nature of labor market, constitute the main topics to be discussed in this context.